Expression of IFNAR1 and IFNAR2 in cattle placenta during early pregnancy. (1st December 2017) - Wang, W; Liu, R; Liang, X; Zhao, Q; Qu, P; Yao, K; Jiang, M; Luo, Y; Zhang, W; Qing, S
Contents: Interferon‐tau (IFNT), a type I interferon, is an antiluteolytic factor secreted by trophoderm during pregnancy. IFNT transmitted signals or stimulated the expression of some factors to build maternal recognition and keep pregnancy by binding its receptors, IFNT receptor 1(IFNAR1) and IFNT receptor 2 (IFNAR2). Up to now, the expression model and roles of IFNAR1 and IFNAR2 in placenta have not been investigated in cattle. In this study, the localization and expression of IFNAR1 and IFNAR2 in the cattle placenta at days 18–50 of pregnancy were detected by histological examination, immunofluorescence staining and real‐time qPCR. The results showed that IFNAR1 mainly distributed in chorioallantoic membrane, endometrial epithelium, cotyledon and caruncle during the early pregnancy of cattle with change in time‐ and position‐dependent. IFNAR1 and IFNAR2 mRNA expression were mainly detected in chorioallantoic membrane and cotyledon, and markedly increased along with pregnancy process. Moreover, the mRNA expression level of IFNAR1 in chorioallantoic membrane and cotyledon was higher than that of IFNAR2. IFNAR mRNA was also expressed in caruncle tissues, which experienced a tendency of decrease from days 21 to 36, followed by increase after days 36. These results provide morphological basis and quantitative data for investigating the roles of IFNAR1 and IFNAR2 on development of cattle placenta and pregnancy maintenance.